Cis occamy sp. nov, the first representative of the Cis bilamellatus species-group (Coleoptera, Ciidae) in the Neotropical region - Rosa-Oliveira, Ayessa; Lopes-Andrade, Cristiano (Zootaxa, 2023)
Cis occamy sp. nov. is described based on specimens collected at six localities within the Atlantic Forest of the South and Southeast Regions of Brazil. It is the first Neotropical species of the Cis bilamellatus species-group, an aggregate of Cis species in which males have a single plate on both the anterocephalic and anterior pronotal edges, females have a pronotum usually widest near the posterior edge and gradually narrowing anteriorly, and both sexes have dual elytral vestiture. Cis occamy sp. nov. is morphologically similar to the Australian Cis australis Blackburn and Cis walkeri Blair, but differs from both in the sparser pronotal punctation and vestiture, and in the males with anterocephalic edge broadly emarginate apically (barely emarginate in C. australis and not emarginate in C. walkeri) and the tegmen subparallel-sided for most of its length (conspicuously sinuous in C. australis and C. walkeri). Available data on host fungi and geographical distribution of the new species are also provided.